Synthesis, characterization, and photocatalytic potential of meso-porphyrins derived from cardanol and vanillin in the veduction of 4-nitrophenol - Martins, Malena; Mapurunga, Leonardo; Avelino de Figueredo Sobrinho, Francisco de Assis; Clemente, Claudenilson; Lomonaco, Diego; Mazzetto, Selma (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
Heterogeneous photocatalysis is a highly relevant industrial process with applications in toxic waste treatment, environmental impact reduction, productivity enhancement, and time and energy savings, aligning with the principles of sustainable chemistry. In recent years, there has been a significant increase in the search for efficient heterogeneous catalysts applicable to a broader range of reactions. In this context, porphyrin-type macromolecules have emerged as strong candidates. Macromolecules are large, complex structures that play fundamental roles in living organisms. Porphyrins, whether of natural or synthetic origin, belong to this class and exhibit structural variations based on their symmetry. Their structures consist of a macrocycle formed by four pyrrole rings linked by methine bridges, which can be symmetric or asymmetric depending on the substituents at the meso and/or β-pyrrolic positions. The internal cavity of these macromolecules allows the addition of substituents and metal ions, classifying them as metalated or metal-free if they are not coordinated. Due to these properties, they are ideal to use in photocatalytic reactions, particularly for their good visible light absorption, fluorescent emission in the red region, and high chemical stability. This work aimed to synthesize a new meso-porphyrin derived from cardanol and vanillin and its zinc (Zn) and copper (Cu) metalated analogs, with potential application in the heterogeneous catalytic photoreduction of 4-nitrophenol (4-NP) in aqueous solutions. The meso-porphyrins-cardanol-vanillin (PCV) and their metalated analogs, Cu-porphyrin-cardanol-vanillin (Cu-PCV) and Zn-porphyrin-cardanol-vanillin (Zn-PCV), were synthesized using cardanol, the main component of cashew nut shell liquid (CNSL), and vanillin, derived from lignin, both sourced from regional biomass, and characterized by 1H NMR, FT-IR, and UV-Vis spectroscopy. The kinetic study of the reduction of 4-NP (a nitro phenolic compound found in wastewater, harmful to fauna, flora, and human health) to 4-aminophenol (4-AP), a less toxic compound, was performed through heterogeneous photo catalysis, following a kinetic first-order model. The reaction used 15 mL of an aqueous solution of 4-NP (10-4 mol L-1) and excess NaBH4 (30 mg; 0.9 mmol) as the reducing agent, with H2(g) evolution observed and the first UV-Vis measurement taken at 0 minutes. Subsequently, Cu-PCV (10 mg) was added, and under constant agitation at room temperature and exposure to UV light (Avant 25 W, 60 Hz, I = 205 mA) from a lamp placed inside a dark box, UV-vis measurements were taken every 30 minutes. For each measurement, 500 μL of the mixture was removed from the beaker and diluted with distilled water in a quartz cuvette (3 mL) to monitor the decrease in the absorbance at 400 nm. The same procedures were followed for the Zn-PCV compound. After each cycle, the composites were collected and washed with distilled water (3 times). The proposed methodology for synthesizing the PCV and its metalated analogs (Zn and Cu) derived from cardanol and vanillin proved to be efficient, as all synthetic steps showed satisfactory yields: precursors (65%), meso-porphyrin (59%), and metalated analogs (Cu-PCV = 89%; Zn-PCV = 73%), while their respective characterizations (1H NMR FT-IR, UV-Vis) revealed a set of peaks and bands confirming their pure forms. The reduction of 4-NP using NaBH4 as a reducing agent involves the formation of the p-nitrophenolate ion and its conversion to 4-AP. However, this does not occur without a catalyst to promote electron transfer, reducing the reaction’s activation energy. The p-nitrophenolate ion shows an absorption band around 400 nm, which gradually decreases in intensity during the reduction reaction using the catalysts. At the same time, a band at 300 nm appears, attributed to the p-aminophenolate ion. Notably, in the presence of NaBH4, the aqueous 4-NP solution changes from yellow to colorless after complete reduction. These results reinforce the positive impact of the catalysts on the efficiency of photocatalytic processes, as the presence of the metal in the meso-porphyrin center increases the separation of photogenerated charges (e-/h+) by electron trapping, thus improving the material’s photocatalytic performance. These compounds successfully achieved the photocatalytic reduction of 4-NP, with Cu-PCV completing the reduction in just 90 minutes, while Zn-PCV converted all 4-NP to 4-AP in 150 minutes. The results demonstrated the effectiveness of the new compounds as renewable catalysts, promoting more sustainable chemistry and showing potential for reducing pollutants in water bodies, offering a feasible solution for wastewater remediation.